Exploring the benefits of a stroke telemedicine programme: An organisational and societal perspective. (December 2016) - Bagot, Kathleen L; Bladin, Christopher F; Vu, Michelle; Kim, Joosup; Hand, Peter J; Campbell, Bruce; Walker, Alison; Donnan, Geoffrey A; Dewey, Helen M; Cadilhac, Dominique A
We undertook a qualitative analysis to identify the broader benefits of a state-wide acute stroke telemedicine service beyond the patient-clinician consultation. Since 2010, the Victorian Stroke Telemedicine (VST) programme has provided a clinical service for regional hospitals in Victoria, Australia. The benefits of the Victorian Stroke Telemedicine programme were identified through document analysis of governance activities, including communications logs and reports from hospital co-ordinators of the programme. Discussions with the Victorian Stroke Telemedicine management were undertaken and field notes were also reviewed. Several benefits of telemedicine were identified within and across participating hospitals, as well as for the state government and community. For hospitals, standardisation of clinical processes was reported, including improved stroke care co-ordination. Capacity building occurred through professional development and educational workshops. Enhanced networking, and resource sharing across hospitals was achieved between hospitals and organisations. Governments leveraged the Victorian Stroke Telemedicine programme infrastructure to provide immediate access to new treatments for acute stroke care in regional areas. Standardised data collection allowed routine quality of care monitoring. Community awareness of stroke symptoms occurred with media reports on the novel technology and improved patient outcomes. The value of telemedicine services extends beyond those involved in the clinical consultation to healthcare funders and the community.